O movimento social feminista: a relevância da noção honnethiana de reconhecimento para a promoção dos direitos das mulheres - Correia, Éllen Cristina Rodrigues (Universidade do Vale do Rio dos Sinos, 2022)
This thesis aims to analyze the relevance of the Honnethian notion of recognition for the promotion of women's rights. Its specific objectives are to understand the history of women and the inequalities they face, to subsequently reconstruct Axel Honneth's theory about the struggle for recognition (the motivation for social conflict, the spheres of recognition) and understand in what ways the theory of recognition relates to gender issues. In addition, we aim to understand how this concept can, or cannot, assist in the advancement of women's rights in contemporary neoliberal society. To achieve these goals, we will explore the work The Struggle for Recognition (2009), by Axel Honneth, as well as other works complementary to the discussion, such as Mary Wollstonecraft's A Vindication of the Rights of Woman (1792/2016) and Gender: Key Concepts in Philosophy, by Tina Chanter (2011), in addition to journalistic material and legal briefs to contextualize the situation of women. That said, the method chosen was the bibliographic research with special attention to the previously mentioned work of Axel Honneth. The results of the research indicate that Honneth’s theory of recognition contributes to the progress of women's rights due to the model of struggle the philosopher elaborated. However, the theory alone will not be able to handle the demands of contemporaneity, thus, it seems that it needs to be combined with a political model that imagines a feminism for the majority and/or does not treat it as a "woman's thing".
Keywords: Reconhecimento; Axel Honneth; Movimento social feminista; Recognition; Feminist movement; ACCNPQ::Ciências Humanas::Filosofia